IMPLEMENTASI ISLAM INA-INA PEDAGANG KELILING DI KECAMATAN PALU BARAT KOTA PALU - Samsinas Samsinas (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
This paper deals with the societal structure where ina-ina live, and its influences toward their religious life, which in turn, gives impacts on their social interaction either in family or social environment. Sociologically, female peddlers (ina-ina) are part of Muslim community in their village. They are responsible for their family and society, establishing social harmony. Although female peddlers are economically poor, they do not want to be burden for the governnent and other people. Their religious commitment becomes a basis of power to survive, living a positif live for the future of their family especially their children. They recognize that this life is a mandate and which should be lived with pleasure. The factors that influence ina-ina female peddlers in such vilages as Tipo, Loli and Kanuna, include economic, social, cultural, educational, political and religious. It is these factors that define ina-ina female peddlers’ religious life.